(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
This article discusses the theoretical and practical foundations of the use of digital technologies in the process of teaching phonetics of the Karakalpak language. The role of digital tools in the effective formation of phonetic knowledge in students, the development of pronunciation and listening skills is analyzed. Also, methodological approaches, platforms, multimedia tools and the advantages of interactive programs are considered.